Long-term survival was achieved through multidisciplinary treatment of a patient with gallbladder carcinosarcoma accompanied by KRAS mutation: a case report and literature review - Liao, Yedan; Lai, Junbo; Yang, Jilan; Long, Tingfeng; Wu, Xi; Luo, Dan; Tan, Jin; Zhang, Ke; Tang, Jiadai; Xie, Lin (Frontiers in Oncology, 2025)
Carcinosarcoma of the gallbladder (CSGB) is an extremely rare subtype of primary gallbladder malignancy, which with a high rate of preoperative misdiagnosis due to its nonspecific clinical symptoms and imaging findings, as well as a high rate of recurrence within a short period of time after surgery, resulting in a very poor prognosis. Through a search of the medical literature, we found that there are few reports of CSGB receiving comprehensive treatments and achieving relatively good outcomes. Here, we report a rare case of CSGB with KRAS G12V mutation that achieved survival time of 32 months after receiving a combination of treatments including surgery, chemotherapy, radiotherapy, and immunotherapy, and we conducted a literature review for the disease with the aim of raising awareness of the disease.